KHALED HOSSEINI'S WORKS, SUCH AS THE KITE RUNNER AND THOUSAND SPLENDID SUNS, EXPLORE THE INNER LIVES AND EMOTIONS OF TEENAGERS. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Khaled Hosseini, an Afghan-American author best known for his novels And the Mountains Echoed, A Thousand Splendid Suns, and The Kite Runner, has a unique gift for exploring the intricacies of interpersonal relationships and emotions. One of his main themes is the inner lives of young people, particularly teenagers, as they navigate the rough waters of identity, love, guilt, and bereavement. Through his remarkably empathetic portrayal of youth, Hosseini offers profound insights into the emotional struggles of adolescents, especially in the backdrop of war and societal expectations.